A Novel Strategy to Enhance Acid Strength of Zeolites by Incorporating Ge into Zeolite Framework. Issue 17 (2nd May 2022) - Kokuryo, Shinya; Jabri, Hasna Al; Miyake, Koji; Uchida, Yoshiaki; Tanaka, Shunsuke; Miyamoto, Manabu; Oumi, Yasunori; Nishiyama, Norikazu
Abstract: In the long history of zeolite research, further enhancement of their acid strength has looked difficult. In this study, we achieved the enhancement by incorporating Ge into the zeolite framework. We synthesised the zeolites by a dry gel conversion method and characterised them in terms of morphology, crystal structure, and composition. We determined the acid strength of these zeolites by calculating the change in the enthalpy of desorption in the temperature‐programmed desorption of ammonia and confirmed that the acid strength of the zeolites with Ge was higher than that of a conventional zeolite. This enhancement of acid strength probably originated from the unprecedented interactions between Al and Ge, unlike the conventional interactions between Al and Si. The enhanced acid strength led to high efficiency of ethanol‐to‐propylene reactions, affording higher yield of propylene than that obtained using conventional zeolites. Abstract : This study is one of the few to develop a strategy that increases the acid strength of zeolites by incorporating Ge. We synthesized the zeolites using a dry gel conversion method and confirmed that the acid strength of the zeolites with Ge was stronger than that of a conventional zeolite. Using the zeolites, we demonstrated one of the highest selectivities (51 %) for propylene in ethanol‐to‐propylene reactions.